Pengembangan Sistem Kasir Berbasis Website Pada "Bang Aji Kebab" Menggunakan Model Agile - Moch Yusuf Anshar; Rinci Kembang Hapsari; Sugiyanto Sugiyanto (KERNEL: Jurnal Riset Inovasi Bidang Informatika dan Pendidikan Informatika, 2025)
The Bang Aji Kebab culinary business in Surabaya continues to experience growth in terms of branch expansion and transaction volume, thus requiring more effective operational management. However, the sales transaction recording process is still carried out manually, which often leads to issues such as recording errors, inaccurate sales data, and delays in preparing financial and stock reports. Based on these problems, a web-based cashier system was developed as a digital solution to support operational processes, transaction recording, and stock analysis automatically, in real time, and in an integrated manner. The development method used is the Agile Model through the timebox planning stage, implemented using the Laravel 11 framework and MySQL database, and tested using the Black-Box Testing method. System quality evaluation refers to the ISO 9126 standard, which includes Usability, Accessibility, Security, and Reliability aspects. The research results show that the system operates according to operational needs, with main features such as product management, cashier transactions, receipt printing, and sales analysis functioning optimally. Functional testing using Black-Box Testing produced results that met expectations, while software quality assessment based on ISO 9126 obtained an average score of 87.25% with a "very good" category. In conclusion, this web-based cashier system is capable of accelerating transaction processes, improving the accuracy of sales recording, and providing sales analysis reports that can support business decision-making more effectively.